Green protocol for the synthesis of N-oxides from secondary amines using vanadium silicate molecular sieve catalyst - Phukan, P.; Khisti, R. S.; Sudalai, A. (Journal of Molecular Catalysis A-Chemical, 2006)
Vanadium silicate molecular sieve catalyst VS-I was found to promote efficiently the oxidation of alpha alpha,alpha'alpha'-tetrasubstituted secondary amines with 30% aqueous hydrogen peroxide as oxidant. In comparison to other catalysts reported to date, this heterogeneous catalyst offers a remarkably simple workup procedure and is reusable without any appreciable loss of activity. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: heterogeneous catalyst; Hydrogen peroxide; N-oxide; VS-1; zeolite